The effect of H2S on internal dry reforming in biogas fuelled solid oxide fuel cells. Issue 2 (16th December 2021) - Wasajja, Henry; Saadabadi, S. Ali; Illathukandy, Biju; Lindeboom, Ralph E. F.; van Lier, Jules. B.; Vellayani Aravind, Purushothaman
Abstract: Internal dry reforming of methane is envisaged as a possibility to reduce on capital and operation costs of biogas fuelled solid oxide fuel cells (SOFCs) system by using the CO2 present in the biogas. Due to envisaged internal dry reforming, the requirement for biogas upgrading becomes obsolete, thereby simplifying the system complexity and increasing its technology readiness level. However, impurities prevailing in biogas such as H2 S have been reported in literature as one of the parameters which affect the internal reforming process in SOFCs. This research has been carried out to investigate the effects of H2 S on internal dry reforming of methane on nickel‐scandia‐stabilised zirconia (Ni‐ScSZ) electrolyte supported SOFCs. Results showed that at 800°C and a CH4 :CO2 ratio of 2:3, H2 S at concentrations as low as 0.125 ppm affects both the catalytic and electric performance of a SOFC. At 0.125 ppm H2 S concentration, the CH4 reforming process is affected and it is reduced from over 95% to below 10% in 10 h. Therefore, future biogas SOFC cost reduction seems to become a trade‐off between biogas upgrading for CO2  removal and biogas cleaning of impurities to facilitate efficient internal dry reforming. Abstract : H2 S at concentration as low as 0.125 ppm greatly affects both the catalytic and electric performance of a SOFC. Therefore, future biogas SOFC cost reduction seems to become a trade‐off between biogas upgrading for CO2 removal and biogas cleaning of impurities to facilitate efficient internal dry reforming.